Riesgo climático para la región arrocera con respecto a Pyricularia oryzae - Martinez, Malvina Irene; Moschini, Ricardo Carlos; Pedraza, Valeria Beatriz (Asociación Argentina de Fitopatólogos (AAF), 2024)
Poster